A novel double-π model for multilayer inductor based on 130 nm SiGe process and modified parameter extraction procedure. Issue 8 (17th November 2019) - Li, Xiuping; Cao, Cheng; Hou, Yajing; Liu, Jiangfan; Wang, Zhe; Xia, Qing; Zhu, Hua
ABSTRACT: In this article, a multilayer inductor for millimeter-wave regime was fabricated based on 130 nm SiGe process with compact size and high quality factor (Q). The area of cross-section for the proposed inductor is 40 μ m × 40 μ m and the highest Q value is 14 at millimeter-wave regime. We present a novel double- π equivalent circuit and a modified parameter extraction method to characterize the multilayer inductor with excellent accuracy over a broad-band frequency up to 110 GHz. To improve the accuracy of circuit model of the multi-layer inductor, mutual coupling between different layers is introduced into the conventional double- π model. Equivalent circuit parameters can be extracted from two-port S -parameters by utilizing the modified simple parameter extraction methodology. Simulation and measured results validate the validity of double- π model and parameter extraction methodology with good accuracy.